What's the abuse? A quest for the appropriate legal test in product design cases under Article 102 TFEU. Issue 3 (June 2019) - Eicher, Florence
In recent years, vastly changing technology markets have posed challenges to the application of well-established rules and principles in European Union competition law. In particular, the integration of technical functionalities appears to have opened new possibilities for dominant firms to leverage market power. Aware of these developments but often oblivious to the apparent overlap, the European Union Commission and the Court of Justice of the European Union engaged in clear-cut analyses under one or the other well-established theory of harm. In particular, the dividing line between the two standalone concepts on refusals to deal and tying practices appears to have been either repositioned or misapplied in the Microsoft Saga, which marks the peak of this development. In classifying the respective conduct as abusive tying practices in the Microsoft Saga, it is questionable whether the Commission was granted a shortcut by the Court itself, passing (unsuccessful) refusal to deal cases disguised as (successful) tying cases. Considering the significantly lower standard of proof applicable to tying practices as opposed to refusals to deal, stakeholders can be expected to exploit the vague boundaries. With this concern in mind, this essay aims to identify the boundaries between refusal to supply and tying cases, where product integration risks resulting in anti-competitive foreclosure on technology markets. On a more fundamental level, this essay will question whether the peculiar features of technology markets justify a different treatment.